2017
DOI: 10.1007/s40273-017-0499-z
|View full text |Cite
|
Sign up to set email alerts
|

How Qualitative Methods Can be Used to Inform Model Development

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 28 publications
(34 reference statements)
0
24
0
Order By: Relevance
“…Previous work has found that there is much scope for augmenting the essential elements of economic evaluation with additional qualitative data to inform the context of the study (Husbands et al, ; Kelly et al, ; Van Voorn et al, ). Additionally, from an individual study perspective, patient narratives have been used to inform a recent U.K. health technology assessment about the emotional, social, and material environments that informed the “push and pull” of financial incentives to modify participants' (pregnant and breastfeeding women that smoke) smoking behaviour (Hoddinott et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous work has found that there is much scope for augmenting the essential elements of economic evaluation with additional qualitative data to inform the context of the study (Husbands et al, ; Kelly et al, ; Van Voorn et al, ). Additionally, from an individual study perspective, patient narratives have been used to inform a recent U.K. health technology assessment about the emotional, social, and material environments that informed the “push and pull” of financial incentives to modify participants' (pregnant and breastfeeding women that smoke) smoking behaviour (Hoddinott et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, there has been a call for health economists to effectively integrate combinations of qualitative and quantitative methods into their research toolkit to enrich their research methodologies and therefore improve their practice in health economic study design, data gathering and analyses, reporting, and ultimately research translation (Coast, ; Coast, Mcdonald, & Baker, ; Husbands, Jowett, Barton, & Coast, ; Kelly, McDaid, Ludbrook, & Powell, ; Obermann, Scheppe, & Glazinski, ; Smith, Mitton, & Peacock, ). Additionally, health policy development, research, and management could benefit from more in‐depth, textured descriptions of what actually happens in practice settings, health care markets, and patients' lives (Greenhalgh et al, ; Weiner, Amick, Lund, Lee, & Hoff, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are examples of different qualitative research methods used for model development including the Delphi technique [12,13], focus groups [8], and stakeholder workshops [14]. Despite their potential, there is limited uptake of formal qualitative methods in model development by modellers and health economists [15].…”
Section: Introductionmentioning
confidence: 99%